Examining the vintage effect in hedonic pricing using spatially varying coefficients models: A case study of single-family houses in the Canton of Zurich - Jakob A. Dambon; Stefan Sebastian Fahrländer; Saira Karlen; Manuel Lehner; Jaron Schlesinger; Fabio Roman Albert Sigrist; Anna Zimmermann (Swiss Journal of Economics and Statistics, 2022)
This article examines the spatially varying effect of age on single-family house (SFH) prices. Age has been shown to be a key driver for house depreciation and is usually associated with a negative price effect. In practice, however, there exist deviations from this behavior which are referred to as vintage effects. We estimate a spatially varying coefficients (SVC) model to investigate the spatial structures of vintage effects on SFH pricing. For SFHs in the Canton of Zurich, Switzerland, we find substantial spatial variation in the age effect. In particular, we find a local, strong vintage effect primarily in urban areas compared to pure depreciative age effects in rural locations. Using cross validation, we assess the potential improvement in predictive performance by incorporating spatially varying vintage effects in hedonic models. We find a substantial improvement in out-of-sample predictive performance of SVC models over classical spatial hedonic models.
Keywords: C31; C53; R31; R32; 330; Gaussian process; Spatial statistics; Real estate; Mass appraisal